Chemical Composition and Lactic Microflora of Adjuevan, A Traditional Ivorian Fermented Fish Condiment - Koffi-Nevry, R.; Ouina, T.S.T.; Koussemon, M.; Brou, K. (Pakistan Journal of Nutrition, 2011)
Adjuevan, a traditional Ivorian naturally fermented fish prepared from the Atlantic bumper Chloroscombrus chrysurus, was assessed for its proximate and lactic acid microflora compositions in order to establish its nutritive and technological usefulness. Significant differences were observed between the fresh and the fermented fish for all the chemical substance analyzed except for the lipid content. Adjuevan contained between 69.65 and 71.25% moisture, 12.16 and 12.36% lipid, 21.21 and 26.81% protein. The mean value for the ash, Ca, P, Na and K content of the adjuevan were 10.5%, 4.16 mg/g, 3.82 mg/g, 0.72 mg/g and 0.67 mg/g respectively. There were no significant differences between samples from the different processors. The genera and species of lactic acid bacteria isolated and identified from the fresh fish and the adjeuvan samples were Leuconostoc lactis, Lactobacillus fermentum, Pediococcus sp., Streptococcus sp. The highest load was obtained with Lactobacillus fermentum, 9.4x103 to 3.7x104 cfu/g. The fermentation does not adversely affect the composition of Chloroscombrus chrysurus. Lactic acid bacteria found could participate in the technological processing and contribute to keeping the quality of the adjuevan.